The intention to adopt Short Messaging Service (SMS) among people with visual impairment from the expanded technology acceptance model perspective: The case of Malaysian Association of Blind (MAB) / Mohd Aidil Riduan Awang Kader ... [et al.] - Awang Kader, Mohd Aidil Riduan; Mohezar Ali, Suhana; Ali, Roslina; Mat Yunus, Nor Khairunnisa; Mohamed Badri, Shamsul Nizam (2013)
People with visual impairment often encounter difficulties as accessibility and mobility in their daily life, with majority of them having communication problems. Challenges of the individual's ability to interact with others, initiate or maintain friendships as well as participate as a member of a community can lead to isolation. Information and communication technology (ICT) has opened new opportunities for people with visual impairment. Technology promises to enable and empower people with vision loss to the same degree as their non-visual impairment peers. The growing ubiquity of mobile phones and short messaging service (SMS) has opened up a range of possibilities for people with visual impairments. There is wide agreement that information and communication technology (ICT) is a valuable tool for people with visual impairment, with various research disciplines have focused on how people with vision loss can reap advantage of the technology available for social, educational and personal purposes. Yet, there is little research on how visually impaired people perceived the short message service (SMS), particularly from the educational perspective. Therefore the objective of this research is to investigate the influence factors that affect people with visual impairment intention to adopt Short Messaging Service (SMS) by applying the expanded technology acceptance model (TAM). The finding discovered that only usefulness has significant relationship with user's behavioral intention of SMS. However, there were lack of support for enjoyment, ease of use and perceived fees on SMS adoption among people with visual impairment particularly at MAB.